Diagnostic Challenges in Metastatic Prostate Adenocarcinoma Using PSMA PET-CT: A Case Report - Rane, Bhushan; Bedarkar, Shivani; Jha, Deepak; Wani, Kishore (Journal of Pharmacy Practice and Community Medicine)
Prostate adenocarcinoma is a common malignancy in elderly males and may present with lower urinary tract symptoms, particularly when advanced or metastatic. We report a 65-year-old male presenting with progressive urinary complaints, chronic low back pain, and generalized weakness. Laboratory evaluation revealed markedly elevated serum prostate-specific antigen levels. Transrectal ultrasound-guided biopsy confirmed prostatic adenocarcinoma with a Gleason score of 4 + 3. Advanced imaging demonstrated metastatic involvement of pelvic lymph nodes and multiple skeletal sites. Prostate-specific membrane antigen positron emission tomography/ computed tomography enabled comprehensive assessment of tumor extent and confirmed disseminated disease. The patient was managed initially with symptomatic therapy and androgen deprivation therapy, followed by bilateral surgical castration after multidisciplinary evaluation. This case highlights the diagnostic challenges associated with advanced prostate carcinoma and emphasizes the clinical value of molecular imaging for accurate staging, prognostication, and therapeutic decision-making. Early recognition and individualized management remain essential to optimize outcomes in metastatic prostate cancer.
Keywords: Bone Metastases; Lower Urinary Tract Symptoms; Metastatic Prostate Cancer; Prostate Adenocarcinoma; Prostate-Specific Membrane Antigen Imaging